The evaluation of Agro climatic potentials of Kermanshah and Isfahan provinces in autumn cultivation of sugar beet (تحقیقات کاربردی علوم جغرافیایی)
Since the most important climatic parameter affecting sugar beet cultivation is the temperature, we carried out this research considering climatic elements such as temperature, precipitation and freezing days in relation to autumn sugar beet planting. Daily temperatures of selected stations in a period of 10 years (2005-2015) has been used for agroclimatic analysis. In order to evaluate that, thermal potential assessment, deviation from optimal conditions and active day gradient index (GDD) were used. The evaluation of thermal potential based on the threshold of 0, 4, and 10 degrees Centigrade at the station levels in Kermanshah province showed that Sar-e-Pol-e-Zahab Station has the highest cumulative thermal unit and Kangavar Station has the least one. In Isfahan province, Khour-va-Biabanak station has the highest cumulative thermal unit and Khansar station has the lowest unit. Based on the deviation from optimal conditions in Kermanshah province, Sar-e-Pol-e-Zahab station has the lowest (-27.79) and in Khour-va-Biabanak station (-21.78) had the least deviation from optimal conditions. Planting date at the stations was considered based on the autumn temperature. In Kermanshah province, Sar-e-Pol-e Zahab station had the earliest date of harvest (May 1st.), while this date in Isfahan province was for Khour-va-Biabanak station (May 9th.). Suitable areas for planting in Kermanshah province are found to be the eastern and northeastern regions of Sar-e-Pol-e Zahab and Qasr-Shirin. In the province of Isfahan, the northern and western parts of Khour-va-Biabanak and Kashan were the most proper regions and central areas are in the next steps.